Mobile Health untuk Mencegah Luka Diabetes: A Systematic Review - Risyda Zakiyah Hanim; Tuti Herawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Ulcus diabeticum is the most common complication that results in death. Diabetic foot currently reach 40 to 60 million people in patients diagnosed with diabetes mellitus. This article was a mobile-health systematic review in preventing diabetic foot injuries. The search sources were Scopus, Science Direct, PubMed, ProQuest, Ebscohost and Sage published from 2015 to 2020 with the search keywords of "diabetes mellitus", "ulcus diabetic", "foot ulcer", "diabetic wound", "prevention", "mhealth", "telehealth ", " telemedicine", and "telenursing". The results show that there were four components in preventing diabetes wounds, namely monitoring foot temperature, foot images, directed guidance and virtual consultation. Mhealth has a positive impact on the prevention of diabetes mellitus wounds so that mHealth can be applied to prevent the incidence of diabetic wounds. Keywords: m-health; prevention; diabetic wounds ABSTRAK Ulkus diabeticum merupakan komplikasi yang paling banyak mengakibatkan kematian. Kaki diabetik saat ini mencapai 40 hingga 60 juta jiwa pada pasien yang terdiagnosa diabetes mellitus. Artikel ini merupakan systematic review mobile-health dalam mencegah luka kaki diabetik. Sumber pencarian adalah Scopus, Science Direct, PubMed, ProQuest, Ebscohost dan Sage yang diterbitkan dari 2015 hingga 2020 dengan kata kunci pencarian "diabetes mellitus", "ulcus diabetic", "foot ulcer", "diabetic wound" "prevention", "mhealth", "telehealth", "telemedicine", dan "telenursing". Hasil menunjukkan terdapat empat komponen dalam pencegahan luka diabetes yakni monitoring suhu kaki, gambar kaki, panduan terarah dan konsultasi virtual. mhealth berdampak positif pada pencegahan luka diabetes mellitus sehingga mHealth dapat memungkinkan untuk diterapkan untuk mencegah kejadian luka diabetes. Kata kunci: mhealth; pencegahan; luka diabetes